Dihydrotanshinone exhibits an anti-inflammatory effect in vitro and in vivo through blocking TLR4 dimerization. (April 2019) - Yuan, Renyikun; Huang, Liting; Du, Li-Jun; Feng, Jian-Fang; Li, Jun; Luo, Ying-Ying; Xu, Qiong-Ming; Yang, Shi-Lin; Gao, Hongwei; Feng, Yu-Lin
Graphical abstract: The schematic of DHT's anti-inflammatory activities in vitro . Abstract: Dihydrotanshinone (DHT), one of the major ingredients of Salvia miltiorrhiza Bunge (Danshen), displays many bioactivities. However, the activity and underlying mechanism of DHT in anti-inflammation have not yet been elucidated. In this study, we investigated the anti-inflammatory activity and molecular mechanism of action of DHT both in vitro and in vivo . Our data showed that DHT significantly decreased the release of inflammatory cytokines tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and IL-1β in lipopolysaccharide (LPS)-stimulated RAW264.7 cells, THP-1 cells, and bone marrow-derived macrophages (BMDMs), and altered the expression of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS). In addition, flow cytometry results indicated that DHT reduced the calcium influx, and generation of reactive oxygen species (ROS), and nitric oxide (NO) generation in LPS-stimulated RAW264.7 cells. Moreover, DHT suppressed the transcription of nuclear factor-κB (NF-κB), the expressions of NF-κB proteins, and nuclear translocation of NF-κB/p65, thereby suggesting that the NF-κB pathway played a role in the anti-inflammatory action of DHT. In addition, DHT attenuated LPS-challenged activator protein-1 (AP-1) activity, resulting from interference of the mitogen-activated protein kinase (MAPK) pathway. The molecular docking simulation of DHT to toll-like receptor 4 (TLR4) suggested that DHT binds to the active sites of TLR4 to block TLR4 dimerization, which was further corroborated by cellular thermal shift assay and co-immunoprecipitation (Co-IP) experiments. Furthermore, the recruitment of myeloid differentiation primary response gene 88 (MyD88) and the expression of transforming growth factor-b (TGF-b)-activated kinase 1 (p-TAK1) were disturbed by the inhibition of TLR4 dimerization. Thus, investigating the molecular mechanism of DHT indicated that TLR4-MyD88-NF-κB/MAPK signaling cascades were involved in the anti-inflammatory activity of DHT in vitro . In in vivo mouse models, DHT significantly ameliorated LPS-challenged acute kidney injury, inhibited dimethylbenzene-induced mouse ear oedema, and rescued LPS-induced sepsis in mice. Taken together, our results indicated that DHT exhibited significant anti-inflammatory activity both in vitro and in vivo, suggesting that DHT may be a potential therapeutic agent for inflammatory diseases.